THE EFFECT OF PICTURE BOOK IN LEARNING THEMES OF OBJECTS AROUND US ON THE STUDENTES LEARNING OUTCOMES IN CLASS V AT SDN KEDURUS 01 SURABAYA - Artinata, Wilda Karina; Masyhud, Sulthon; Wardoyo, Arik Aguk (EduStream: Jurnal Pendidikan Dasar, 2022)
This research is an experimental research, pattern quasi-experimental and non-equivalent control group. The purpose of this study was to determine whether or not there was a significant effect of using picture book in learning the theme of objects around us on learning outcomes for fifth grade students at SDN Kedurus 01 Surabaya. The subjects in this study were fifth grade students at SDN Kedurus 01 Surabaya. The research was carried out in the odd semester of 2022/2023. Data collection methods using observation, interviews, tests, and documentation. Data analysis technique is the homogeneity test, t-test, relative effectiveness test. The use of SPSS version 25.0 data processing program to be a tool in analyzing data. It is shown that the research results obtained are that there is a significant effect of using picture book in learning the theme of objects around us on the learning outcomes of fifth grade students at SDN Kedurus 01 Surabaya. The t-test shows that the tcount 6.26. The calculation results show that tcount > ttable (6.26 > 1.67), then the null hypothesis is rejected (H0) and the alternative hypothesis is accepted (H1), while 48.67% of the results obtained from the relative effectiveness test (ER) is included in the medium category.